THE EFFECT OF BEETROOT (Beta vulgaris L.) JUICE ON CHOLINESTERASE ACTIVITY IN FARMERS EXPOSED TO ORGANOPHOSPHATE PESTICIDES - Devyana Dyah Wulandari; Andreas Putro Ragil Santoso; Devyani Diah Wulansari (JURNAL INDONESIA DARI ILMU LABORATORIUM MEDIS DAN TEKNOLOGI, 2019)
A decrease in cholinesterase (chE) enzyme activity is an indicator of pesticide poisoning, especially organophosphate pesticides. The chE activity reduction will result in an increase in the amount of acetylcholine and will bound to muscarinic and nicotinic receptors in the central and peripheral nervous system which can lead to the onset of Alzheimer's disease. However, antioxidant products can slow the progression of Alzheimer's disease by protecting neurons from oxidative stress. Red Beetroot (Beta vulgaris L.) contains betalains and phenolic compounds which act as an antioxidants that are capable of preventing such illness. This study aims to prove the concept that antioxidant compounds in red beetroot juice can increase the chE activity in subjects exposed to organophosphate pesticides. This research is an observational study with an experimental approach. This research used 25 farmers who were exposed to organophosphate pesticides as respondents. They were given 500 ml of beetroot juice twice a day for 2 consecutive months. Cholinesterase levels were measured before and after consuming red beet juice. Measurement of cholinesterase levels was carried out using a kinetic photometric test. This method was developed based on recommendations from the German Society of Clinical Chemistry (DGKC). The results showed that the average of chE (U/L) Level Before Treatment was 8.102 and 8.380 after treatment with a p value 0,62. It can be concluded that there was an increase in the level of cholinesterase but it was not statistically significant. This may be caused by a different response to activity of cholinesterase after consuming beetroot juice in each subjects, age difference, smoking habits, and personal protective equipment.